PHYSICOCHEMICAL AND SENSORY CHARACTERISTICS OF EFFERVESCENT PINEAPPLE HEALTH DRINKS AT VARIOUS SODIUM BICARBONATE CONCENTRATIONS - Oktaviani, Sulha Rahmi; Dewi, Yohana S.K.; Lestari, Oke Anandika (Jurnal Sains Mahasiswa Pertanian, 2020)
Instant food products are preferred by the public because they are easily consumed and stored. One functional food product in the form of a health drink is Effervescent. Pineapple effervescent can support food diversification programs. The aim of this research was to determine the best sodium bicarbonate concentration based on physicochemical and sensory characteristics of effervescent contains core and flesh pinapple. This research used one-factor randomized block design (RBD), with 7 levels concentration, 10%, 15%, 20%, 25%, 30%, 35%, 40 sodium bicarbonate. The result showed that the best formulation of pineapple effervescent based on physicochemical and sensory characteristics was 20% sodium bicarbonate. The result of the best formulation of pinapple effervescent has moisture (6.24%), ash (15.01%), total soluble solid (7.93Â°Brix), solubility (13.83 seconds), pH (6.65) Vitamin C (130,13 mg/100g), potassium (0,22%), flavour (4,3), foam appearance (4,5), sweetness (3,7) bitterness (2,5), and effectiveness index (0,54). Pineapple effervescent sensory tested by QDA (Quantitative Descriptive Analysis), Method showed that seven samples are not much different according to foam appearance, aroma, sweetness and bitterness parameters.Keywords : bicarbonate, effervescent, pineapple.